Modeling and multiscale characterization of the quantitative imaging based fibrosis index reveals pathophysiological, transcriptome and proteomic correlates of lung fibrosis induced by fractionated irradiation - Zhou, Cheng; Moustafa, Mahmoud; Kriegsmann, Mark; Schwager, Christian; Bäuerle, Tobias; Schnölzer, Martina; Debus, Jürgen; Abdollahi, Amir (International journal of cancer, 2019)
Pulmonary fibrosis represents a leading cause of morbidity and mortality worldwide. Therapy induced lung fibrosis constitutes a pivotal dose-limiting side effect of radiotherapy and other anticancer agents. We aimed to develop objective criteria for assessment of fibrosis and discover pathophysiological and molecular correlates of lung fibrosis as a function of fractionated whole thoracic irradiation. Dose-response series of fractionated irradiation was utilized to develop a non-invasive and quantitative measure for the degree of fibrosis - the fibrosis index (FI). The correlation of FI with histopathology, blood-gas, transcriptome and proteome responses of the lung tissue was analyzed. Macrophages infiltration and polarization was assessed by immunohistochemistry. Fibrosis development followed a slow kinetic with maximum lung fibrosis levels detected at 24-week post radiation insult. FI favorably correlated with radiation dose and surrogates of lung fibrosis i.e., enhanced pro-inflammatory response, tissue remodeling and extracellular matrix deposition. The loss of lung architecture correlated with decreased epithelial marker, loss of microvascular integrity with decreased endothelial and elevated mesenchymal markers. Lung fibrosis was further attributed to a switch of the inflammatory state toward a macrophage/T-helper cell type 2-like (M2/Th2) polarized phenotype. Together, the multiscale characterization of FI in radiation-induced lung fibrosis (RILF) model identified pathophysiological, transcriptional and proteomic correlates of fibrosis. Pathological immune response and endothelial/epithelial to mesenchymal transition were discovered as critical events governing lung tissue remodeling. FI will be instrumental for deciphering the molecular mechanisms governing lung fibrosis and discovery of novel targets for treatment of this devastating disease with an unmet medical need.
First published: 11 December 2018
Gesehen am 03.07.2019